2022
DOI: 10.1001/jamanetworkopen.2022.11071
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Colorectal Surgery During the COVID-19 Pandemic

Abstract: Ever since its widespread outbreak, the COVID-19 pandemic has challenged health care systems worldwide. Allocation of resources in an effort to contain the spread of the virus, along with the reluctance of many patients to seek health care because of restrictions and social isolation, have severely disrupted preventive screenings and cancer care worldwide. Beds were needed for critically ill patients with COVID-19, and staff were required to care for those patients. Therefore, a resource transfer led to a proh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The pandemic altered the allocation of resources towards treating the SARS-COV-2 pandemic displayed a greater influx of SARS-COV-2 related microbiology orders. Even so, this population pool did not display an overall decrease in diagnosis of CRC during the pandemic when compared to the years prior as originally anticipated (Freund & Wexner, 2022). Well to moderately differentiated is categorized under moderately differentiated The cases that tested positive for E. faecalis one of the adenocarcinomas is noted to have neuroendocrine differentiation * Indicates one patient tested positive for these microorganisms and this result was not shared by any other patients.…”
Section: Limitationsmentioning
confidence: 80%
“…The pandemic altered the allocation of resources towards treating the SARS-COV-2 pandemic displayed a greater influx of SARS-COV-2 related microbiology orders. Even so, this population pool did not display an overall decrease in diagnosis of CRC during the pandemic when compared to the years prior as originally anticipated (Freund & Wexner, 2022). Well to moderately differentiated is categorized under moderately differentiated The cases that tested positive for E. faecalis one of the adenocarcinomas is noted to have neuroendocrine differentiation * Indicates one patient tested positive for these microorganisms and this result was not shared by any other patients.…”
Section: Limitationsmentioning
confidence: 80%
“…The study included the year 2020, when the COVID-19 pandemic was declared; in this regard, several studies have reported that during the initial phase of the pandemic, there was a significant decline in both the total number of surgical interventions and the number of surgeries conducted for colorectal cancer [ 35 ]. In contrast to those findings, which have shown a notable reduction in the management of cancer patients during the COVID-19 pandemic, efforts were made in our unit to maintain the same level of surgical care for colorectal cancer patients during that period of time.…”
Section: Discussionmentioning
confidence: 99%
“…These circumstances occurred because national recommendations issued during the COVID-19 pandemic made it clear that non-emergent surgical circumstances should be postponed until a negative PCR test from the patient is received. Other studies, however, reported that both the overall number of surgical interventions and the colorectal cancer surgeries decreased significantly, at least in the initial phase of the pandemic [ 31 ]…”
Section: Discussionmentioning
confidence: 99%